Relation Betwen Tongue Dimensions and Lower Incisorr Crowding - Metin ORHAN; Ahmet YAĞCI; Faruk İzzet UÇAR; Melike Büşra ALAN; Tancan UYSAL (Galenos Yayinevi, 2012)
Aim:The aim of this study was to evaluate the relationship between the tongue dimension measurements and lower incisor crowding/position and to identify the possible gender differences.Subjects and Method:Forty-five pretreatment plaster models and cephalometric radiographs of Class I patients taken by a standard technique formed the sample for this study. The sample of this study included 22 male (mean age: 15.67±1.41 years) and 23 female (mean age: 13.86±1.35 years) patients. Lower incisor crowding was measured with the Little irregularity index. Multivariate statistical analysis was used at p<0.05 level. To evaluate the correlation between tongue area and lower incisor crowding/position; Pearson correlation coefficients (r) were estimated.Results:Statistically significant gender differences were determined in tongue area (p=0.001). There was no statistically significant difference for the tongue measurements among subjects with different levels of crowding. In female group, significant correlations were determined between tongue area, L1-NB (mm) (r= 0.457; p=0.029) and L1-NB (⁰) (r= -0.447; p=0.032) measurements. In male group, significant correlations were determined between incisor crowding, L1-NB (mm) (r= -0.590; p=0.004), L1-NB (⁰) (r= -0.638; p=0.001) and L1-mandibular plane (⁰) (r= - 0.505; p=0.017).Conclusion:No relationship was found between tongue measurements and different levels of mandibular incisors crowding. Statistically significant correlation was found between tongue area and mandibular incisors position for both genders. Beside this, males showed significant inverse correlation between irregularity index and mandibular incisors position.